(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
This paper examines motives and barriers of Adults Learners in Initial Vocational Education in Greece. The research involved 80 participants who attended educational programs at publics I.E.K. in Greece. The data collection was carried out by using the PRB Questionnaire (Participation-Reason-Barriers). The results of this study showed that participants attend education programs/seminars in order to become more efficient in their work, to obtain certificate of attendance and to satisfy their interest in learning. The efficiency at work was introduced as the most significant motive. On the other hand, barriers that prevent participation in a seminar/ program are the cost of participation, the lack of transport to the seminar venue, the lack of information and lack of awareness of seminars held; among these barriers the most important one, is the cost of participation.